International Transfer Credit: Indonesia International MBKM Curriculum Based on Authenticity - Retno Mawarini Sukmariningsih; Eko Nursanty; Inti Englishtina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Credit Transfer International is a prestigious program that is the hope of all Indonesian students so far. This activity provides an opportunity for Indonesian students to study on campuses abroad for one semester as grant recipients from the Ministry of Education, Culture, Research and Technology. Although a student successfully goes through the selection process and officially becomes a student on an international campus, it does not mean all problems have been resolved. Various problems often arise both regarding learning efforts, curriculum and intercultural surprises that often arise. This research is exploratory, based on the experience in lecturers while guiding students of Credit Transfer participants and participants of activities for two years in the period 2020 and 2021. The results of this study found elements forming students' competing abilities in the international learning process that are strongly influenced by local culture before the activities of their respective campuses. The local culture in question is something that needs to be developed under the concept of local learning that has been taught by the father of Education Ki Hajar Dewantara. The development of bloom's modern pedagogy theory has been shown to shape the Competency-Based Curriculum in students. This research proves that collaboration with local pedagogy a la Ki Hajar Dewantara has created a sustainable International MBKM Curriculum through strengthening IKU 2 (Students Get Off-Campus Experience) and IKU 6 (Study Program in collaboration with world-class Partners).